ARE ASPECTS OF THE PHYSICAL ENVIRONMENT IMPORTANT IN DETERMINING THE GUEST EXPERIENCE? THE STUDY OF THE APURVA KEMPINSKI BALI - Irene Andrayani; Efin Shu (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
The physical environment is found to be one of the manifestations that shape guest experience. The purpose of this research is to find out the influence of the physical environment on guest experience (GE) with the moderation of hotel cleanliness (HC) at The Apurva Kempinski Bali. The physical environment in this research focused on three variables, which are hotel ambiance (HA), hotel layout (HL), and hotel furnishing (HF). This research uses a quantitative approach. Data is collected through the distribution of a Google Form questionnaire. The population for this research is unknown in numbers. The Lemeshow formula is used to determine a minimal sample size of 97 individuals, and the final sample collected was 103 respondents. All questionnaire statements have successfully passed the validity and reliability tests conducted using SPSS 27. Additionally, with SmartPLS 4, the data has passed the outer model test. The P-value for the direct effects of hotel ambiance and hotel furnishing on guest experience shows significant results. However, the P-value for the direct effect of hotel layout on guest experience shows insignificant results. The moderating effects of hotel cleanliness between the physical environment elements and guest experience also show insignificant results. The recommendation for The Apurva Kempinski Bali is to maintain the hotel's ambiance and furnishing to elevate the guest experience.